Legal Implications of the Merauke Food Estate: A Critical Analysis of Customary Rights and Environmental Concerns - Finda Pratiwi Yuwono (Lex Publica, 2024)
The Food Estate program in Merauke, part of Indonesia's National Strategic Project (PSN), aims to enhance food security through large-scale land management. However, its implementation has faced significant criticism for disregarding the Free, Prior, and Informed Consent (FPIC) principle, leading to violations of the rights of Indigenous Peoples and severe environmental degradation, including extensive deforestation. The involvement of military personnel in facilitating the program further complicates the situation, drawing international scrutiny, particularly in light of Indonesia's participation in COP29. This study employs a normative legal research method with a qualitative approach, analyzing secondary data from various sources, including laws, regulations, books, journals, and online resources. The findings reveal that the Merauke Food Estate program exhibits substantial flaws in planning and execution, neglecting sustainable development principles and the FPIC standard. The study also suggests that conflict resolution mechanisms, such as class action lawsuits, could be a viable solution, provided these processes are grounded in FPIC principles and actively involve MHA to ensure equitable outcomes for affected communities.